Análisis bioestratigráfico y paleoambiental de la caldera La Primavera, Jalisco - Dorantes Zavaleta, Rosa Lilia (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
The La Primavera Caldera (CLP) located in the western sector of the Trans-Mexican Volcanic Belt, has the relicts of the existence of an ancient lake developed in its interior during the Pleistocene, within the isotopic stage MIS 5 (a and b), during an interglacial period characterized by warm and semi-arid environmental conditions. The Primavera ancient lake began ?90Ka (Stage 1), as a body of shallow water with scarce diatoms characterized by Campylodiscus clypeus, Mastogloia smithii, Entonomeis paludosa and Achnantes minutissima, indicating conditions of high ionic concentration in a macrophyte rich lake. Centrales diatoms found at the top of this sequence (Cyclotella meneghiniana and Pseudocylotella primaverensis) suggest a short increase in water level. For the 89.8 ka the arrival into the lake of a giant pumice interrupts its development; the algae material analyzed within the matrix of this horizon corroborated a body of shallow water. Successively the extrusion of the Nejahuete dome divided the lacustrine sequence in two bodies the South Central lake and the North lake. In Stage 2, sedimentation was reinitiated in both paleo-lakes, being more fluviodeltaic in the Northern zone, while in the South Central region, a more stable lake dominated by silty-clayed sedimentation, with Cyclotella m and Pseudocyclotella p.as dominating diatoms indicating and a slight increase in depth and alkalinity conditions into the lake. In the northern area the detrital contribution decreased permitting the diatoms development with central diatoms Achnantes minutissima dominating, suggesting a shallow lake of Na-rich, neutral-alkaline waters, with moderate to high conductivity and presence of springs. For Stage 3, lacustrine sedimentation in the northern zone was replaced by a fluvial system dominated by sand deposits with interbedded ash.

La Caldera La Primavera (CLP) ubicada en el sector Oeste de la Faja Volcánica Transmexicana, posee los relictos de la existencia de un antiguo lago desarrollado en su interior durante el Pleistoceno, dentro del estadio isotópico MIS 5 (a y b), caracterizado por un periodo interglacial de condiciones ambientales cálidas y semiáridas. El paleolago de la Primavera inició hace ?90Ka (Estadio 1), como un cuerpo de agua somero con escasas diatomeas pennales destacando Campylodiscus clypeus, Mastogloia smithii, Entonomeis paludosa y Achnantes minutissima, que indican condiciones de alta concentración iónica del agua y la presencia de macrofitas. Especies centrales encontradas en la cima de esta secuencia (Cyclotella meneghiniana y Pseudocylotella primaverensis) sugieren un pobre incremento en el tirante de agua. Para los 89.8 ka el ingreso al lago de una Pómez Gigante interrumpe su desarrollo; el material algareo analizado dentro de la matriz de este horizonte corroboró un cuerpo de agua somero. Posteriormente el emplazamiento del domo el Nejahuete dividió la secuencia lacustre en dos cuerpos el lago Sur Central y el lago Norte. En el Estadio 2 se reinició la sedimentación en ambos lacustres siendo más fluviodeltaica en la zona Norte, mientras que en la región Sur Central, se desarrolló un lago más estable con sedimentación limoarcillosa donde abundan Cyclotella m. y Pseudocyclotella p. indicando alcalinidad y un ligero aumento de la profundidad. En el área norte el aporte volcanoclástico y la sedimentación lacustre disminuyó; las diatomeas centrales dominan junto con Achnantes minutissima, lo que sugiere un lago somero de aguas ricas en Na, neutro- alcalinas, con moderada a alta conductividad y presencia de manantiales. Para el Estadio 3, la sedimentación lacustre en la zona norte se substituyó por un sistema fluvial dominado por depósitos de arenas con cenizas intercaladas.
Instituto de Investigaciones en Ciencias de la Tierra. Maestría en Geociencias y Planificación del Territorio
Keywords: info:eu-repo/classification/cti/1; INICIT-M-2018-0246; Pómez gigante; Nejahuete; Diatomeas; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4408